ASSESSMENT OF ENVIRONMENTAL SENSITIVITY TO DESERTIFICATION WITH MEDALUS MODEL IN GIS IN MAYMONA PROJECT- SOUTH OF IRAQ - & et al., Hamad (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
The objective of this study was to identify the locations sensitivity to land desertification based on the Mediterranean Desertification and Land Use (MEDALUS) approach by the Geographic Information Systems (GIS) in the south of Maysan governorate at Iraq for mapping environmentally sensitive areas to desertification. Three indicators, which included climate, vegetation, and soil, were employed to estimate the ESAI and then to classify the land in critical, fragile potentially, and non-influenced sensitive areas. The results of the soil quality index (SQI) indicated that 25% of the studied area was classified as moderate quality and 21% was low quality while 54% was very low quality. Vegetation qualities were classified into moderate and low quality 19% and 81%, respectively, and climate quality was classified as moderate.